ANALISIS HUKUM TERHADAP STATUS HARTA GONO-GINI YANG DIJAMINKAN SETELAH PERCERAIAN: Legal Analysis Of The Status Of Marital Property (Gono-Gini) Used As Collateral After Divorce - Daulay, R. Fahmi Natigor; Muhammad, Ade Sultan (Ganec Swara, 2025)
Joint property (gono-gini) or marital property refers to property acquired by spouses during marriage based on Article 35 of Law No. 1 of 1974 on Marriage. In practice, complex issues arise when such joint property is used as collateral in financial institutions, followed by divorce. This study analyzes the legal responsibility of spouses toward joint property used as collateral after divorce and its settlement mechanism. The research method employs a normative juridical approach with qualitative analysis of relevant legislation. The findings indicate that legal responsibility remains jointly applicable despite divorce, and property division can only be conducted after debt obligations are settled first to protect the rights of both parties and creditors.